Contribution of mathematics anxiety, achievement motivation, and academic potential to problem solving ability - Putra, Desak M. P. D.; Ardana, I Made; Astawa, I W. P. (Jurnal Pendidikan dan Pengajaran, 2019)
The purpose of this research was to determine the contribution of mathematics anxiety, achievement motivation, and potential academic towards mathematics problem solving ability. The population of this research was 3791 students at class VII public junior high school in Denpasar City. The sample of this study consisted of 483 students who were obtained using proportionate cluster random sampling. The type of this research was ex post facto with path analysis technique. The data of mathematics anxiety and achievement motivation were collected by questionnaires, while the data of potential academic and mathematics problem solving ability were collected by tests. Results showed that (1) mathematics anxiety directly affected potential academic in inverse correlation with contribution of 24.2%, (2) achievement motivation directly affected potential academic in positive correlation with contribution of 62.4%, (3) mathematics anxiety directly affected mathematics problem solving ability in inverse correlation with contribution of 43.1%, (4) mathematics anxiety directly affected mathematics problem solving ability in positive correlation with contribution of 2.6%, (5) achievement motivation directly affected mathematics problem solving in positive correlation with contribution of 41.2%, (6) achievement motivation indirectly affected mathematics problem solving ability in positive correlation with contribution of 6.7%, (7) potential academic directly affectedÂ  mathematics problem solving ability in positive correlation with contribution of 10.7%, (8) mathematics anxiety and achievement motivation simultaneously affected potential academic in positive correlation with contribution of 69.2% (9) mathematics anxiety, achievement motivation, and potential academic simultaneously affected mathematics problem solving ability in positive correlation with contribution of 79.4%.